SUMOylation balance: a key determinant in synapse physiology - Bertozzi, Alessia; Toscanelli, Walter; Castellitto, Giuditta; Grassi, Claudio; Colussi, Claudia (Frontiers in Physiology, 2025)
Neuronal communication relies on the precise regulation of synaptic compartments, where protein activity, localization, and turnover are tightly controlled. Among the mechanisms ensuring this regulation, post-translational modifications (PTMs) play a central role. SUMOylation, the covalent attachment of Small Ubiquitin-like Modifier (SUMO) proteins to target substrates, has emerged as a dynamic key PTM in the nervous system, modulating synaptic structure and function. Target SUMOylation occurs through an enzymatic cascade and requires the presence of a consensus sequence. Reversible addition of SUMO monomers or chains may contribute to distinct functional outcomes changing the conformation of the protein thus favoring/inhibiting molecular interaction among proteins or stabilizing the protein inhibiting degradation or influencing subcellular localization. All these SUMO dependent effects are crucial in the regulation of the tiny and highly specialized synaptic compartments to achieve spatiotemporal control for proper neurotransmission and synaptic plasticity in response to environmental stimuli. Dysregulation of this system has been implicated in various neurological disorders, including Alzheimer’s disease, where imbalances in SUMO1 versus SUMO2/3 levels contribute to synaptic dysfunction. As such, comprehension of SUMO related mechanisms may give important insights into both physiological regulation of synapses and potential therapeutic approaches for neurodegenerative diseases. Thus, in this review we will first introduce the enzymatic cascade of SUMOylation and its impact on protein function, then we will focus on its role within the synaptic compartment. Finally, we will discuss the therapeutic potential of modulating SUMOylation in Alzheimer’s disease as example of neurodegenerative disorders.